2011
DOI: 10.3382/ps.2010-01082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amino acid formulation and supplementation on nutrient mass balance in turkeys

Abstract: Nutrient mass balances were determined for turkeys fed 4 diets in a 2 × 2 factorial design to investigate the effects of diets with 100 or 110% of NRC (1994)-recommended amino acid (AA) formulation and diets containing 2 (Lys and Met) or 3 (Lys, Met, and Thr) supplemental AA. Hybrid tom turkeys were raised and monitored in 12 rooms (3 replicates/diet; 20 toms/room at hatch, culled to 16 at 21 d and then to 12 at 28 d of age). All feed and litter entering and leaving the rooms were quantified and analyzed for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The findings also demonstrate that although dietary treatments may reduce losses in the form of gaseous emissions, litter or excreta composition may not reflect the differences in gaseous losses that occur, and therefore may not serve as an indicator of the potential for reducing air emissions by using feeding methods (Liu et al, 2011).…”
Section: Nutritional Treatmentmentioning
confidence: 93%
See 2 more Smart Citations
“…The findings also demonstrate that although dietary treatments may reduce losses in the form of gaseous emissions, litter or excreta composition may not reflect the differences in gaseous losses that occur, and therefore may not serve as an indicator of the potential for reducing air emissions by using feeding methods (Liu et al, 2011).…”
Section: Nutritional Treatmentmentioning
confidence: 93%
“…The lower pH shifts develops more ammonium ion (NH 4 + ). The study of Liu et al (2011) showed that diets containing three supplemental amino acids resulted in lower nitrogen excretion (by 12%) and a lower cumulative loss of ammonia (by 23%) when compared with diets containing only two supplemental amino acids.…”
Section: Nutritional Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from Trial 2 showed an increase in N retention and a decrease in NH 3 emissions per bird in response to reduced dietary CP. Powers and Angel (2008) reported a 15% reduction in NH 3 emissions as a result of reducing dietary CP by 2 percentage points, and numerous studies support the trend towards reduced NH 3 from lower CP diets (Elwinger and Svensson 1996;Corzo et al 2005;Powers and Angel 2008;Liu et al 2011). Reduced NH 3 emissions result in lower indirect N 2 O emissions.…”
Section: Mitigation Of Gaseous Emissionsmentioning
confidence: 98%
“…Reducing dietary crude protein (CP) has been effective in reducing NH 3 (Elwinger and Svensson 1996;Corzo et al 2005;Powers and Angel 2008;Liu et al 2011). Mitigation focussed on litter management by increasing the litter depth has shown reduced NH 3 emissions (Al Homidan et al 1997).…”
Section: Introductionmentioning
confidence: 99%